Buddhist Principles appearing in the Succession Tradition of the Thai Lue People, Muang Ngoen, Xayaburi Province, People’s Democratic Republic of Laos - Wenkham, Phra Oudom; Vongmaly, Phra Boun Ouane; Unsaun, Sittichai (Journal of Thammawat, 2024)
The objectives of this article were: 1) to study the history of the fate inheriting tradition of Thai Lue people, Muang Ngoen, Xayaburi province, People’s Democratic Republic of Laos, 2) to study Buddhist mantra chant which occurred in the tradition of inheriting the fate of Thai Lue people, Muang Ngoen, Muang Ngoen, Xayaburi province, People’s Democratic Republic of Laos, 3) Analyze Buddhist principles found in the tradition of inheriting the fate of the Thai Lue people, Muang Ngoen, Muang Ngoen, Xayaburi province, People’s Democratic Republic of Laos. This research was qualitative research, studied documents and fieldwork to gather data and interview and analyzed the data descriptively. The results of the research had found that the history of the destiny tradition of the Tai Lue people, Mueang Ngen, Xayaburi Province, was based on two beliefs: 1) Buddhism was the origin of the destiny tradition with beliefs about renewal from Buddhist literature. 2) It was a belief that arose only for the individual, it was the belief of a person who believed in the matter of magic and auspicious spells or astrology. That performed the fate ceremony would dispel all dangers from one’s body and heal from existing illnesses. Buddhist mantras were what create faith and belief in their power to cure suffering, sorrow, sickness, and restlessness, and to eliminate dangers. The principles that appeared in the fate-descending tradition of the Tai Lue people, Mueang Ngen, Xayaburi Province, were inserted into the Dhamma scriptures that were used in the sermon for the destiny-descending ceremony. Two principles appeared, namely the principle of miracles 3 and the principle of merit-making 3.